Development Status and Future Prospects of Hydrogen Fuel Cell Technology - Liu Yingdu (《中国工程科学》杂志社, 2021)
Hydrogen fuel cell is a key element for conversing hydrogen energy into electric power and has attracted increasing attention from the aspects of basic research and industrial application following the proposal of carbon neutral and carbon peaking. Focusing mainly on the hydrogen fuel cell technology system, we analyze the research progress and development trends of membrane electrode components (such as proton exchange membranes, electrocatalysts, and gas diffusion layers), bipolar plates, system components, and control strategies. Subsequently, we propose the development directions of the hydrogen fuel cell technology system by 2035, following the analysis of the development status of the hydrogen fuel cell technology in China in terms of localization rate, system lifetime, power density, and manufacturing cost. To accelerate the application of hydrogen energy and hydrogen fuel cell technology, we suggest that research on hydrogen production technology should be strengthened to reduce the cost of hydrogen fuel, the technological research and application of key materials and core components should be accelerated, and industrial plans with increased investment should be formulated to establish a complete policy support system.